2022
DOI: 10.20961/placentum.v10i1.54822
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting With the Prevalence of Hypertension in Pregnancy: Scoping Review

Abstract: <p><strong>Background:</strong> Hypertension is a clinical term to describe the pressure of high blood which cause fetal morbidity due to reduced blood flow to the placenta, such as stunted fetal growth, fetal death in utero to premature birth to cause maternal morbidity such as pulmonary edema, bleeding in the brain, eclamptic seizures, blood clots in the veins, acute kidney failure and even death in the mother. Hypertension in Pregnancy is a major complication that causes 60% to 80% of mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(22 reference statements)
1
3
0
Order By: Relevance
“…In terms of maternal age, most of the mothers included in the study were young as the majority of them were below 35 years old, which is similar with previous studies conducted by Khuan et al in Malaysian public hospitals [16]. Maternal age has been established as an important risk factor for HDP as it affects the reproductive process during pregnancy [10]. The current study re ects this idea as the prevalence of HDP is found to be higher for women with advanced maternal age (≥ 35 years old) compared to younger women.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In terms of maternal age, most of the mothers included in the study were young as the majority of them were below 35 years old, which is similar with previous studies conducted by Khuan et al in Malaysian public hospitals [16]. Maternal age has been established as an important risk factor for HDP as it affects the reproductive process during pregnancy [10]. The current study re ects this idea as the prevalence of HDP is found to be higher for women with advanced maternal age (≥ 35 years old) compared to younger women.…”
Section: Discussionsupporting
confidence: 76%
“…The increasing trend in the prevalence of HDP over 11 years from 2012 to 2023 could be multifactorial, including the obesity pandemic driven by the increasing rate of poor eating habits and a sedentary lifestyle. Considering obesity being established as an important risk factor of HDP [10], the observed elevated prevalence in Malaysia could be in uenced by the increasing rate of obesity among the Malaysian population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations